APLIKASI BIBLIOKONSELING SEBAGAI SALAH SATU STRATEGI MEMBANTU KLIEN DALAM KONSELING - Muh. Yusuf Hidayat (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2008)
Counseling as technology of humanistic help needs appropriate strategy, so service subject gets advantage for itself. Bibliocounseling constitutes one of the help strategies by using information in the source library. This strategy can be made use of helping the client to improve health and so on. In order that, the counselor needs expansion bibliocounseling: goal, characteristic, client’s problem, material, method, and evaluation. The result of bibliocouseling has been planned that can be presented with technique of self-management, minimal contact, management counselor, and counselor’s direction. Its application, of course, it pays attention of principle such as truth and powerfulness information, efficient, advantage, client activity, and interest.